Lithium secondary battery and method for manufacturing same

By using specific materials in the positive and negative electrodes of lithium secondary batteries and adjusting their efficiency constants, the problem that lithium secondary batteries are difficult to maintain long life and fast charging performance while improving energy density, and high energy density and excellent life characteristics are achieved.

CN119522496APending Publication Date: 2025-02-25LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380052055.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2023-09-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

While improving the energy density, existing lithium secondary batteries are difficult to maintain long life and fast charging performance.

Method used

By using specific lithium composite transition metal compounds and silicon-based active materials and carbon-based active materials in the positive electrode and the negative electrode, and adjusting their efficiency constants to satisfy specific mathematical formulas, the efficiency balance between the positive electrode and the negative electrode is achieved.

Benefits of technology

The high energy density of lithium secondary batteries is achieved, while significantly improving the battery life and fast charging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229460910000131
    Figure BDA0005229460910000131
  • Figure BDA0005229460910000141
    Figure BDA0005229460910000141
Patent Text Reader

Abstract

Disclosed is a lithium secondary battery comprising a positive electrode, a separator, and a negative electrode, in which the positive electrode contains a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co), and the negative electrode contains a silicon-based active material and a carbon-based active material, the efficiency constants of the silicon-based active material and the carbon-based active material and the efficiency constant of the lithium composite transition metal compound satisfy a specific mathematical formula.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium secondary battery and a method for manufacturing the same.

[0002] This application claims the priority of Korean Patent Application No. 10-2022-0131766 filed in the Korean Intellectual Property Office on September 30, 2022, the entire contents of which are incorporated herein by reference. Background Art

[0003] Secondary batteries are widely used not only in portable devices but also in electric vehicles (EVs) and hybrid electric vehicles (HEVs) driven by an electric drive source.

[0004] Since such secondary batteries have not only the major advantage of being able to significantly reduce the use of fossil fuels but also the advantage of not generating any byproducts due to the use of energy, secondary batteries have attracted attention as a new energy source that is environmentally friendly and improves energy efficiency.

[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, etc. In addition, the electrodes (such as the positive electrode and the negative electrode) may have an electrode active material layer provided on a current collector.

[0006] As the use of secondary batteries increases, various battery performances are required. Although attempts to change the composition of the electrode active material layer in order to improve battery performance have been appropriately made, some performances of the battery can be improved according to the selection or combination of materials, but some performances may be deteriorated instead. Therefore, it is necessary to study the selection or combination of materials suitable for improving the performance of secondary batteries. Summary of the invention

[0007] [Technical issues]

[0008] The present invention is directed to providing a lithium secondary battery having high energy density and excellent lifespan characteristics.

[0009] [Technical solution]

[0010] One aspect of the present invention provides a lithium secondary battery comprising: a positive electrode, a separator and a negative electrode,

[0011] The positive electrode comprises a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co).

[0012] The negative electrode comprises a silicon-based active material and a carbon-based active material, and

[0013] When the efficiency constants of the silicon-based active material and the carbon-based active material are a and b, respectively, based on 100 parts by weight of the total amount of the silicon-based active material and the carbon-based active material, the weight of the silicon-based active material is a*, and the efficiency constant of the lithium composite transition metal compound is c, a, a*, b and c satisfy the following mathematical formula 1:

[0014] [Mathematical formula 1]

[0015] [(a×a*)+{b×(100-a*)}] / c>103.5.

[0016] Another aspect of the present invention provides a method for manufacturing a lithium secondary battery, comprising:

[0017] forming a positive electrode including a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co),

[0018] forming a negative electrode comprising a silicon-based active material and a carbon-based active material,

[0019] forming a lithium secondary battery including the positive electrode and the negative electrode; and

[0020] When the efficiency constants of the silicon-based active material and the carbon-based active material are a and b, respectively, based on 100 parts by weight of the total amount of the silicon-based active material and the carbon-based active material, the weight of the silicon-based active material is a*, and the efficiency constant of the lithium composite transition metal compound is c, a, a*, b and c are adjusted to satisfy the following mathematical formula 1:

[0021] [Mathematical formula 1]

[0022] [(a×a*)+{b×(100-a*)}] / c>103.5.

[0023] [Beneficial Effects]

[0024] According to the aspects described in the present specification, high energy density can be achieved by selecting materials with excellent charging and discharging efficiency as active materials for the positive and negative electrodes. At the same time, by adjusting the efficiency constant and content according to the types of active materials contained in the positive and negative electrodes so that the efficiency constant and content satisfy a specific mathematical formula, a balance of efficiency between the positive and negative electrodes can be achieved, thereby improving the battery life and fast charging performance. DETAILED DESCRIPTION

[0025] Hereinafter, the present invention will be described in more detail to help understand the present invention. The present invention can be implemented in various forms, not limited to the aspects described herein. In this case, the terms or words used in the specification and claims should not be interpreted as limited to the conventional meaning or dictionary meaning, but should be interpreted as having the meaning and concept consistent with the technical idea of ​​the present invention based on the principle that the inventor can appropriately define the concept of the term in order to best describe his invention.

[0026] In the present invention, the terms "include", "comprising" or "having" are intended to indicate the existence of implemented features, quantities, steps, constituent elements or any combination thereof, and should be understood as not excluding the possibility of the existence or addition of one or more other features or quantities, steps, constituent elements or any combination thereof.

[0027] The case where a part (such as a layer) exists “above” or “on” another part includes not only the case where the part exists “directly” “above” another part, but also the case where another part exists between them. Conversely, the case where a part exists “directly” “above” another part means that no other part exists between them. In addition, the case of being “above” or “on” a reference part means being located above or below the reference part, and does not necessarily mean being “above” or “on” in a direction opposite to gravity.

[0028] In this specification, “primary particles” refer to particles having no crystal boundaries in appearance when observed at a magnification of 5000 to 20000 times using a scanning electron microscope.

[0029] In the present specification, "secondary particles" are particles formed by agglomeration of primary particles.

[0030] In this specification, single particle is a term used to distinguish a single particle from positive electrode active material particles in the form of secondary particles formed by agglomeration of tens to hundreds of primary particles generally used in the prior art, and is a concept that includes single particles composed of one primary particle and agglomerate particles of less than 10 primary particles.

[0031] In the present specification, the "particle" may mean any one or all of a single particle, a secondary particle, and a primary particle.

[0032] A lithium secondary battery in one aspect of the present invention comprises a positive electrode, a separator and a negative electrode, wherein the positive electrode comprises a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co), the negative electrode comprises a silicon-based active material and a carbon-based active material, and when the efficiency constants of the silicon-based active material and the carbon-based active material are a and b respectively, based on 100 parts by weight of the total amount of the silicon-based active material and the carbon-based active material, the weight of the silicon-based active material is a*, and the efficiency constant of the lithium composite transition metal compound is c, a, a*, b and c satisfy the following mathematical formula 1.

[0033] [Mathematical formula 1]

[0034] [(a×a*)+{b×(100-a*)}] / c>103.5.

[0035] The value of mathematical formula 1 can be calculated to a value with one decimal place.

[0036] The inventors of the present invention recognize that in order to achieve high energy density of the battery, it is necessary to design efficient positive electrode materials and negative electrode materials with good charge / discharge efficiency. However, when a silicon-based active material with a large capacity per unit weight is used as a negative electrode material, there is a problem of low efficiency leading to degradation of the negative electrode, so that the long-term life characteristics deteriorate. Therefore, the inventors of the present invention have found that while using efficient silicon-based active materials as negative electrode active materials, lithium nickel cobalt compounds are used as positive electrode active materials. However, when specific efficiency parameters are met, the long life can be affected by adjusting the efficiency balance between the positive electrode and the negative electrode, thereby completing the present invention. Specifically, the above-mentioned components contained in the positive electrode and the negative electrode can satisfy Mathematical Formula 1 to achieve a high energy density battery, while improving the efficiency balance between the positive electrode and the negative electrode to prevent degradation of the initial negative electrode and significantly improve the life characteristics.

[0037] According to one aspect, the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) may be a single particle.

[0038] According to one aspect, the silicon-based active material may be a silicon-carbon composite or a silicon oxide, and the carbon-based active material may be graphite. The lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) may contain 80 mol % or more, for example 80 mol % or more and less than 100 mol % of nickel in the metal other than lithium. When the nickel content is high as described above, the positive electrode efficiency can be improved to achieve a high energy density of the battery.

[0039] According to one aspect, the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) may further include at least one of manganese and aluminum. Specifically, the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) may be represented by the following Chemical Formula 1.

[0040] [Chemical formula 1]

[0041] Li a Ni (1-x-y) Co x M1 y M2 w O2

[0042] In Chemical Formula 1,

[0043] 1.0 ≤ a ≤ 1.5, 0 ≤ x ≤ 0.2, 0 ≤ y ≤ 0.2, 0 ≤ w ≤ 0.1, 0 ≤ x + y ≤ 0.2,

[0044] M1 is at least one metal selected from Mn and Al, and

[0045] M2 is one or more metal elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo.

[0046] The average particle size (D50) of the lithium composite transition metal compound can be 12 μm to 30 μm, such as 13 μm to 28 μm, 15 μm to 25 μm, 17 μm to 23 μm. The BET specific surface area of the lithium composite transition metal compound can be 0.5 m 2 / g to 1.1 m 2 / g, such as 0.6 m 2 / g to 1 m 2 / g, or 0.7 m 2 / g to 0.9 m 2 / g. The composition ratio, average particle size (D50), BET surface area, etc. of the lithium composite transition metal compound affect the efficiency constant c of the lithium composite transition metal compound.

[0047] According to one aspect, based on 100 parts by weight of the positive electrode active material, the positive electrode may contain 90 parts by weight to 100 parts by weight of a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co), such as more than 92 parts by weight, more than 94 parts by weight, more than 96 parts by weight, more than 98 parts by weight, or 98 parts by weight to 100 parts by weight.

[0048] In this specification, the silicon-carbon composite is a composite of Si and C, and can also be expressed as an Si / C-based active material, and is distinguished from silicon carbide represented by SiC. The silicon-carbon composite can be a composite of silicon, graphite, etc., or can form a structure in which a core such as a silicon and graphite composite is surrounded by graphene or amorphous carbon. The silicon dispersed in the silicon-carbon composite can be nano-silicon.

[0049] The silicon oxide can be referred to as SiO x (0 < x < 2), and can be silicon-based composite particles containing SiO x (0 < x < 2) and pores.

[0050] SiO x (0 < x < 2) can be the matrix in the silicon-based composite particles. SiO x (0 < x < 2) can be in the form including Si and SiO2, where Si can also form a phase. That is, x corresponds to the ratio of the number of O to Si contained in SiO x (0 < x < 2).

[0051] The average particle size (D 50 ) of the silicon-based active material can be 2 μm to 15 μm, specifically 3 μm to 13 μm, and more specifically 4 μm to 12 μm. When the above range is satisfied, the side reaction between the silicon-based composite particles and the electrolyte can be controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved. In addition, the size of the Si grains contained in the silicon-based active material can be 10 nm to 30 nm, for example 15 nm to 25 nm.

[0052] The composition ratio of the elements constituting the silicon-based active material, the presence or type of the coating layer on the particle surface, the average particle size (D50), the size of the Si grains, etc. affect the efficiency constant a of the silicon-based active material.

[0053] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve of the particles. For example, the average particle size (D 50 ) can be measured using the laser diffraction method. The laser diffraction method can generally measure the particle size in the sub-micron region to about several millimeters and can obtain results with high reproducibility and high resolution.

[0054] In this specification, the "grain size" can be quantitatively analyzed using X-ray diffraction analysis (XRD) of Cu Kα X-rays.

[0055] In this specification, the "specific surface area" is measured by the BET method. Specifically, the specific surface area can be measured by degassing the object to be measured at 130 °C for 2 hours and performing N2 adsorption / desorption at 77 K using a BET measurement device (BEL-SORP-mini, Nippon Bell).

[0056] According to one aspect, the discharge efficiency of the silicon-based active material is 85% to 95%.

[0057] The charge capacity and discharge capacity of the negative electrode and the positive electrode active material can be measured as follows.

[0058] First, active material: Super-C (trademark) conductive material: carboxymethyl cellulose (CMC) thickener: styrene butadiene rubber (SBR) binder polymer were added to water at a weight ratio of 95:1:1:3 to prepare a slurry, and a copper foil was coated with the slurry, punched and calendered to an area of ​​1.4875 cm 2 , and then dried to make an electrode. The electrode assembly is manufactured by using lithium metal as a counter electrode together with the electrode and inserting a polypropylene separator therebetween. After preparing a non-aqueous electrolyte by mixing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7 and adding vinylene carbonate, 1M LiPF6 is added to an organic solvent so that the concentration is 1% by weight, and then by injecting the non-aqueous electrolyte into the electrode assembly to prepare a coin half cell (CHC).

[0059] When charging the coin half cell (CHC) manufactured above, a constant current is applied at a rate of 0.2C until 0.005V by the constant current-constant voltage (CC-CV) method, and then the current is controlled at a constant voltage of 0.005V, and during the discharge process, the discharge efficiency can be measured by the constant current (CC) method at a rate of 0.2C and cut off at 1.5V.

[0060] The silicon-based active material can be used as the percentage of the discharge capacity to the charge capacity measured as the active material, i.e. [discharge capacity (硅类) / Charging capacity (硅类) ×100] is defined as the efficiency constant a, and the carbon-based active material can be used as the percentage of the discharge capacity to the charge capacity measured by the active material, that is, [discharge capacity (碳类) / Charging capacity (碳类) ×100] is defined as the efficiency constant b, and the positive electrode active material can be used as the percentage of the discharge capacity to the charge capacity measured by the active material, that is, [discharge capacity (镍钴类) / Charging capacity (镍钴类) ×100] is defined as the efficiency constant c.

[0061] According to one example, a may be 70 to 85, such as 75 to 80, b may be 85 to 98, such as 90 to 95, and c may be 85 to 90, such as 86 to 89.

[0062] According to one aspect, based on 100 parts by weight of the negative electrode active material, the content of the silicon-based active material can be 1 part by weight to 20 parts by weight. In addition, based on the total amount of 100 parts by weight of the silicon-based active material and the carbon-based active material, the content of the silicon-based active material can be 1 part by weight to 20 parts by weight, for example, 2 parts by weight to 18 parts by weight, 3 parts by weight to 15 parts by weight, 3 parts by weight to 10 parts by weight. When the content of the silicon-based active material is 1% by weight or more, the capacity gain can be above a certain level, and the advantage of using the material can be obtained. When the content is 20% by weight or less, excessive expansion can be prevented, which is advantageous in terms of life and battery characteristics, and is price competitive in terms of cost.

[0063] According to one aspect, the graphite contained in the negative electrode can be natural graphite, artificial graphite or a mixture thereof. Based on 100 parts by weight of the active material contained in the negative electrode, the content of graphite can be more than 80 parts by weight and less than 99 parts by weight, such as 85 parts by weight to 98 parts by weight, 87 parts by weight to 97 parts by weight, 92 parts by weight to 96 parts by weight. When the graphite contains both artificial graphite and natural graphite, the content ratio of artificial graphite to natural graphite can be 5:5 to 9:1, such as 6:4 to 8:2 or 7:3. The average particle size (D50) of artificial graphite can be 5μm to 20μm, such as 6μm to 18μm, or 7μm to 15μm, or 8μm to 12μm, and the average particle size (D50) of natural graphite can be 5μm to 30μm, such as 7μm to 28μm, or 10μm to 27μm, or 12μm to 26μm, or 15μm to 25μm.

[0064] According to one aspect, a negative electrode may include: a current collector; and a negative electrode active material layer disposed on the current collector.

[0065] Based on 100 parts by weight of the negative electrode active material layer, the content of the negative electrode active material can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 88 parts by weight or more and 99 parts by weight or less, 90 parts by weight or more and 98 parts by weight or less, and more preferably 95 parts by weight or more and 99.9 parts by weight or less.

[0066] According to one aspect of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the silicon-based active material and the carbon-based active material.

[0067] The negative electrode binder can be used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode current collector. As the negative electrode binder, a binder known in the art can be used, and its non-limiting examples may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and hydrogen therein is replaced by Li, Na, Ca, etc., and various copolymers thereof may also be included.

[0068] The content of the negative electrode binder may be 0.1 parts by weight to 20 parts by weight, for example, preferably 0.3 parts by weight to 20 parts by weight, and more preferably 0.5 parts by weight to 10 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0069] The negative electrode active material layer may not contain a conductive material, but may contain a conductive material if necessary. The conductive material contained in the negative electrode active material layer is not particularly limited, as long as the conductive material has conductivity and does not cause chemical changes in the battery, for example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, etc. Based on 100 parts by weight of the negative electrode active material layer, the content of the conductive material in the negative electrode active material layer may be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight.

[0070] For the purpose of the present invention, when the carbon-based active material is graphite (e.g., natural graphite or artificial graphite), the weight parts of graphite used as the carbon-based active material are not taken into account when defining the total weight parts of the conductive material. Similarly, when the conductive material selected according to the negative electrode is graphite, the weight parts of the conductive material described are not included when defining the total weight parts of the carbon-based negative electrode active material. Therefore, when graphite is selected as the carbon-based negative electrode active material and the negative electrode conductive material, the total weight parts of graphite correspond to the sum of the weight parts of graphite used as the carbon-based negative electrode active material and the weight parts of graphite used as the negative electrode conductive material.

[0071] The conductive material contained in the negative electrode active material layer is, for example, carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes.

[0072] In one aspect of the present specification, the thickness of the negative electrode active material layer may be 5 μm or more and 500 μm or less.

[0073] In one aspect of the present application, the negative electrode current collector is not particularly limited as long as the negative electrode current collector has conductivity without causing chemical changes in the battery. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. Specifically, a transition metal (such as copper or nickel) that adsorbs carbon well can be used as a current collector. Although the thickness of the current collector can be 1 μm to 500 μm, the thickness of the current collector is not limited thereto.

[0074] In one aspect of the present specification, the positive electrode includes a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co). The thickness of the positive electrode active material layer may be 20 μm or more and 500 μm or less.

[0075] There is no particular limitation on the positive electrode current collector, as long as the current collector has conductivity without causing chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode current collector can generally be 1 to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine concavoconvex objects on the surface of the current collector. For example, the positive electrode current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0076] In one aspect, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 99.9 parts by weight or less.

[0077] According to another aspect of the present specification, the positive electrode active material layer may further include a positive electrode binder and a conductive material.

[0078] The positive electrode binder can be used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material particles and the positive electrode current collector. As the positive electrode binder, a binder known in the art can be used, and its non-limiting examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one or a mixture of two or more thereof can be used.

[0079] The content of the positive electrode binder may be 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, and more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.

[0080] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation as long as it has electronic conductivity without causing chemical changes in the battery. Specific examples thereof include: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.

[0081] Specifically, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). Based on 100 parts by weight of the positive electrode active material layer composition, the content of the conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.

[0082] In addition to using the above-mentioned positive electrode active material and negative electrode active material, the positive electrode and the negative electrode can be manufactured by the manufacturing method of the positive electrode and the negative electrode in the prior art. Specifically, after the composition for forming the active material layer containing the aforementioned active material and the optional binder and the conductive material is coated on the current collector, the positive electrode and the negative electrode can be manufactured by drying and rolling the current collector. In this case, the types and contents of the positive electrode active material and the negative electrode active material, the binder and the conductive material are as described above. The solvent may be a solvent commonly used in the art, examples of which include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc., and any one or a mixture of two or more thereof may be used. As long as the amount of the solvent can dissolve or disperse the active material, the conductive material and the binder in consideration of the coating thickness and the preparation yield of the slurry, and has a viscosity that can show excellent thickness uniformity in the subsequent coating process of the positive and negative electrodes, the amount of the solvent is sufficient. Alternatively, by another method, the positive electrode and the negative electrode may be manufactured by casting the active material layer-forming composition on a separate support and then by laminating a film obtained by peeling off the support on a current collector.

[0083] The diaphragm separates the negative electrode from the positive electrode, and provides a path for the movement of lithium ions, and can be used without particular limitation, as long as it is generally used as a diaphragm in a secondary battery, in particular, it is preferred to have an excellent ability to retain moisture in an electrolyte and to have a diaphragm with low resistance to the movement of ions in the electrolyte. Specifically, a porous polymer film can be used, such as a porous polymer film formed by a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof. In addition, conventional porous nonwoven fabrics can also be used, such as nonwoven fabrics made of glass fiber, polyethylene terephthalate fiber, etc. with a high melting point. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0084] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used to prepare lithium secondary batteries, but are not limited thereto.

[0085] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0086] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.

[0087] In particular, among carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates can be preferably used because cyclic carbonates as high-viscosity organic solvents have high dielectric constants and thus dissociate lithium salts well, and these cyclic carbonates can be more preferably used because cyclic carbonates can be mixed with low-viscosity and low-dielectric-constant linear carbonates (e.g., dimethyl carbonate and diethyl carbonate) in an appropriate ratio and used to prepare an electrolyte with high conductivity.

[0088] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily soluble in a non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN- and (CF3CF2SO2)2N - .

[0089] In the electrolyte, in order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, one or more additives may be included, such as halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0090] A lithium secondary battery of one aspect of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and may be a lithium secondary battery.

[0091] Another aspect of the present invention provides a battery module including the above-mentioned lithium secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include secondary batteries having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as a power source for medium and large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0092] Since the lithium secondary battery of one aspect of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the lithium secondary battery can be used as a power source for portable devices (such as mobile phones, laptops and digital cameras) and medium and large equipment (selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems). For example, the battery module or battery pack can be used as a power source for one or more of the following medium and large equipment: power tools; electric vehicles, including electric vehicles (EV), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEV); and power storage systems.

[0093] Another aspect of the present invention provides a method for manufacturing a lithium secondary battery, comprising:

[0094] forming a positive electrode including a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co),

[0095] forming a negative electrode comprising a silicon-based active material and a carbon-based active material,

[0096] forming a lithium secondary battery including a positive electrode and a negative electrode; and

[0097] When the efficiency constants of the silicon-based active material and the carbon-based active material are a and b, respectively, based on 100 parts by weight of the total amount of the silicon-based active material and the carbon-based active material, the weight of the silicon-based active material is a*, and the efficiency constant of the lithium composite transition metal compound is c, a, a*, b and c are adjusted to satisfy the following mathematical formula 1:

[0098] [Mathematical formula 1]

[0099] [(a×a*)+{b×(100-a*)}] / c>103.5

[0100] The steps of adjusting a, a*, b and c to satisfy equation 1 may include:

[0101] forming a positive electrode including a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co),

[0102] forming a negative electrode comprising a silicon-based active material and a carbon-based active material,

[0103] forming a half-cell comprising a positive electrode or a negative electrode, a counter electrode and an electrolyte;

[0104] Measuring the charge and discharge capacity of a half-cell; and

[0105] The efficiency constant is calculated using the following mathematical formula 2:

[0106] [Mathematical formula 2]

[0107] Efficiency constant = [discharge capacity / charge capacity].

[0108] The description of the lithium ion battery described above can be applied to the description of the positive electrode, the negative electrode, and the efficiency constant of the method for manufacturing a lithium secondary battery of the above aspect.

[0109] [Example]

[0110] In the following, preferred aspects will be given to facilitate understanding of the present invention, but these aspects are provided only for illustrating the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical ideas of the present invention, and such changes and modifications naturally also fall within the appended claims.

[0111] Example 1

[0112] The negative electrode active material layer forming composition includes a negative electrode active material containing SiO and graphite (the weight ratios of SiO and graphite are a* and (100-a*) respectively), a conductive material (carbon black, CNT), a binder (SBR) and a thickener (CMC) in a weight ratio of 95.6:1.0:2.3:1.1, and a copper foil having a thickness of 10 μm is coated with the negative electrode active material layer forming composition to have a dry thickness of 140 μm, and then dried to manufacture a negative electrode. Here, the particle size (D50) of SiO is 10 μm, and the size of the Si crystal grain is 20 nm. The above-mentioned graphite includes artificial graphite and natural graphite in a weight ratio of 7:3, and the average particle sizes (D50) of artificial graphite and natural graphite are 10 μm and 20 μm, respectively.

[0113] The positive electrode active material layer forming composition contains Li in a weight ratio of 97:1:2. 1.0 Ni 0.86 Co 0.06 Mn 0.08 A lithium nickel oxide of O2, a binder (PVDF) and a conductive material (CNT) are prepared, and an aluminum foil having a thickness of 15 μm is coated with the positive electrode active material layer-forming composition to have a dry thickness of 130 μm, and then dried to manufacture a positive electrode. Here, the particle size (D50) of the lithium nickel oxide is 20 μm, and the BET is 0.8 μm. 2 / g.

[0114] The positive electrode and the negative electrode are stacked together with the separator inserted therebetween, and the electrolyte is injected to manufacture the battery. A 12 μm thick separator having a coating layer containing Al2O3 and a PVDF binder is provided on a PE / PP / PE three-layer structure base film, and as the electrolyte, 1M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio 3 / 7) and vinyl carbonate (VC) / propane sultone (PS) (based on 100 parts by weight of the electrolyte, the contents are 3 parts by weight and 1.5 parts by weight, respectively).

[0115] The values ​​of the above Mathematical Formula 1 of the manufactured battery are shown in Table 1. In order to measure the room temperature life and high temperature life of the manufactured battery, the following Table 2 shows the capacity retention rate during 200 cycles of charge and discharge under the following conditions.

[0116] *Room temperature life: The fabricated cells were cycled by charging at 0.33C constant current / constant voltage (CC / CV) to 4.2V (0.05C cutoff) and discharging at 0.5C constant current (CC) (2.5V cutoff) at room temperature (25°C).

[0117] * High temperature life: The fabricated cells were cycled by charging at 0.33C constant current / constant voltage (CC / CV) to 4.2V (0.05C cutoff) and discharging at 0.33C constant current (CC) (2.5V cutoff) at high temperature (45°C).

[0118] * Fast charge life: Charges from 0% SOC to 80% SOC in 25 minutes and discharges at 0.33C constant current (CC) (2.5V cut-off).

[0119] Example 2

[0120] The experiment was conducted in the same manner as in Example 1, except that a silicon carbon composite (Si / C) was used in place of SiO in the negative electrode active material. Here, the particle size (D50) of the silicon carbon composite was 10 μm, and the size of the Si crystal grain was 20 nm.

[0121] Comparative Example 1

[0122] In addition to using Li 1.0 Ni 0.84 Co 0.08 Mn 0.08 Lithium nickel oxides replace Li O 1.0 Ni 0.86 Co 0.06 Mn 0.08 The experiment was conducted in the same manner as in Example 1 except that the lithium nickel oxide contained O2. Here, the particle size (D50) of the lithium nickel oxide was 10 μm, and the BET was 1.2 μm. 2 / g.

[0123] Comparative Example 2

[0124] In addition to using Li 1.0 Ni 0.84 Co 0.08 Mn 0.08 Lithium nickel oxides replace LiO2 1.0 Ni 0.86 Co 0.06 Mn 0.08 The experiment was conducted in the same manner as in Example 1 except that a lithium nickel oxide of 0.02% was used and a silicon carbon composite (Si / C) was used instead of SiO in the negative electrode active material. Here, the particle size (D50) of the lithium nickel oxide was 10 μm and the BET was 1.2 μm. 2 / g.

[0125] Comparative Example 3

[0126] In addition to using Li 1.0 Ni 0.84 Co 0.08 Mn 0.08Lithium nickel oxides replace LiO2 1.0 Ni 0.86 Co 0.06 Mn 0.08 The experiment was conducted in the same manner as in Example 1 except that the weight ratio of SiO* in the negative electrode active material was 3. Here, the particle size (D50) of the lithium nickel oxide was 10 μm, and the BET was 1.2 μm. 2 / g.

[0127] [Table 1]

[0128]

[0129] [Table 2]

[0130]

[0131] As shown in Table 2, it can be confirmed that the capacity retention ratios in Examples 1 and 2 after 200 cycles at room temperature and high temperature and after 50 cycles of rapid charging are excellent compared with the Comparative Example.

Claims

1. A lithium secondary battery comprising: a positive electrode, a separator and a negative electrode, in, The positive electrode comprises a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co), The negative electrode comprises a silicon-based active material and a carbon-based active material, and When the efficiency constants of the silicon-based active material and the carbon-based active material are a and b, respectively, based on 100 parts by weight of the total amount of the silicon-based active material and the carbon-based active material, the weight of the silicon-based active material is a*, and the efficiency constant of the lithium composite transition metal compound is c, a, a*, b and c satisfy the following mathematical formula 1: [Mathematical formula 1] [(a×a*)+{b×(100-a*)}] / c>103.

5.

2. The lithium secondary battery according to claim 1, wherein The silicon-based active material is a silicon-carbon composite or silicon oxide, and the carbon-based active material is graphite.

3. The lithium secondary battery according to claim 1, wherein The lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) contains 80 mol % or more of nickel in metals other than lithium.

4. The lithium secondary battery according to claim 1, wherein The lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) is represented by the following Chemical Formula 1: [Chemical formula 1] The a Nor (1-x-y) Co x M1 y M2 w O2 In Chemical Formula 1, 1.0≤a≤1.5, 0≤x≤0.2, 0≤y≤0.2, 0≤w≤0.1, 0≤x+y≤0.2, M1 is at least one metal selected from Mn and Al, and M2 is one or more metal elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo.

5. The lithium secondary battery according to claim 2, wherein: The discharge efficiency of the silicon-carbon composite is 85% to 95%.

6. The lithium secondary battery according to claim 2, wherein: The positive electrode includes 90 to 100 parts by weight of the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co), based on 100 parts by weight of the positive electrode active material.

7. The method for manufacturing a lithium secondary battery according to any one of claims 1 to 6, comprising: forming a positive electrode including a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co), forming a negative electrode comprising a silicon-based active material and a carbon-based active material, forming a lithium secondary battery including the positive electrode and the negative electrode; and When the efficiency constants of the silicon-based active material and the carbon-based active material are a and b, respectively, based on 100 parts by weight of the total amount of the silicon-based active material and the carbon-based active material, the weight of the silicon-based active material is a*, and the efficiency constant of the lithium composite transition metal compound is c, a, a*, b and c are adjusted to satisfy the following mathematical formula 1: [Mathematical formula 1] [(a×a*)+{b×(100-a*)}] / c>103.

5.

8. The method for manufacturing a lithium secondary battery according to claim 7, wherein: The steps of adjusting a, a*, b and c to satisfy equation 1 include: forming a positive electrode including a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co), forming a negative electrode comprising a silicon-based active material and a carbon-based active material, forming a half-cell comprising the positive electrode or the negative electrode, a counter electrode and an electrolyte; measuring the charge capacity and discharge capacity of the half-cell; and The efficiency constant is calculated using the following mathematical formula 2: [Mathematical formula 2] Efficiency constant = [discharge capacity / charge capacity].

Citation Information

Patent Citations

  • A technology for analyzing interactions between proteins and screening drugs based on protein nanopores

    KR1020220131766A